Adsorbent and its manufacturing method
Patent Information
- Application Number
- JP2021038428
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-10
- Publication Date
- 2025-03-06
- Estimated Expiration
- 2041-03-10
AI Technical Summary
【0008】 本発明の実施形態により、河川や湖沼、海などの水域の水質改善において長期にわたって利用可能な吸着材、およびその製造方法を提供することができる。また、植物の育成に対して効果を有する肥料を低コストで製造することが可能となる。さらに、大気中の二酸化炭素を炭素という形で地中に貯留し、温室効果の抑制に寄与することができる。
Smart Images

Figure 0007641141000001 
Figure 0007641141000002 
Figure 0007641141000003
Abstract
Description
[Technical field]
[0001] One embodiment of the present invention relates to an adsorbent and a method for producing the same. [Background technology]
[0002] It is known that an adsorbent in which iron is supported on a porous carbide having carbon prepared from biomass as a basic material can adsorb phosphate ions derived from phosphoric acid, and can therefore be used to improve the water quality in water areas such as rivers, lakes, and oceans. In addition, since the adsorbent with phosphate ions adsorbed thereon can also be used as a fertilizer, it is possible to effectively utilize the carbon dioxide fixed by plants and store the carbon dioxide in the soil by spreading the adsorbent after phosphate ion adsorption on the soil. Therefore, adsorbents obtained from biomass play a central role in carbon storage for fixing greenhouse gases in the atmosphere (see Patent Document 1 and Non-Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2007-75706 A [Non-patent literature]
[0004] [Non-Patent Document 1] Akira Shibata, "Simple carbonization of biomass and carbon storage vegetables for regional development" Journal of High Temperature Society, March 2011, Vol. 37, No. 2, pp. 37-42 Summary of the Invention [Problem to be solved by the invention]
[0005] An object of one embodiment of the present invention is to provide an adsorbent and a method for producing the same. Alternatively, an object of one embodiment of the present invention is to provide an adsorbent that can be used for water quality improvement and can maintain its shape in water for a long period of time and a method for producing the same. Alternatively, an object of one embodiment of the present invention is to provide a system for storing carbon through fixation of atmospheric carbon dioxide. [Means for solving the problem]
[0006] One embodiment of the present invention is an adsorbent comprising a porous carbide, a binder, and iron, the adsorbent further comprising at least one of a carbonate and a bicarbonate of a metal selected from an alkali metal and an alkaline earth metal.
[0007] One embodiment of the present invention is a method for producing an adsorbent material, comprising mixing porous carbide with a binder and iron powder to prepare a precursor, and treating the precursor with a gas comprising carbon dioxide. Effect of the Invention
[0008] According to the embodiment of the present invention, it is possible to provide an adsorbent that can be used for a long period of time to improve the water quality of water bodies such as rivers, lakes, and oceans, and a method for producing the same. It is also possible to produce fertilizers that are effective for plant growth at low cost. Furthermore, it is possible to store carbon dioxide in the atmosphere in the form of carbon underground, thereby contributing to the suppression of the greenhouse effect. [Brief description of the drawings]
[0009] [Figure 1] 1 is a flowchart showing a method for producing an adsorbent according to one embodiment of the present invention. [Diagram 2] 1 is a scheme showing a method for producing an adsorbent according to one embodiment of the present invention. [Diagram 3] FIG. 1 is a conceptual diagram showing a carbon dioxide storage system according to an embodiment of the present invention. [Figure 4]Photograph of the adsorbent after phosphoric acid adsorption in an example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, each embodiment of the present invention will be described with reference to the drawings, etc. However, the present invention can be embodied in various forms without departing from the gist of the present invention, and should not be construed as being limited to the description of the embodiments exemplified below.
[0011] First Embodiment In this embodiment, an adsorbent and a method for producing the same according to one embodiment of the present invention will be described. 1. Adsorbent The adsorbent has a porous carbide as a basic skeleton, and iron (zero-valent iron) is supported on the surface and pores of the porous carbide. The supported iron causes phosphoric acid and its ions present in water to become iron phosphate, which is then adsorbed to the porous carbide. This allows the adsorbent to be used as an adsorbent for effectively improving the water quality of bodies of water such as rivers, lakes, and oceans. The adsorbent further contains a binder, and also contains at least one of a carbonate and a hydrogen carbonate of a metal selected from an alkali metal and an alkaline earth metal. The adsorbent may further contain an iron compound, or may contain a compound of a metal selected from an alkali metal and an alkaline earth metal other than the carbonate and the hydrogen carbonate, or water.
[0012] 1-1.Porous carbide Porous charcoal is a charcoal produced by using organic matter as a raw material and heating and carbonizing the organic matter under conditions of low oxygen concentration. An example of the organic matter is biomass. Examples of porous charcoal derived from biomass include charcoal, bamboo charcoal, white charcoal, black charcoal, sawdust charcoal, coconut shell charcoal, and rice husk charcoal. As described later, by using biomass as a raw material for porous charcoal, it is possible to construct a system for storing carbon dioxide in the atmosphere and to provide ions of alkali metals and alkaline earth metals that act as reaction sites to prevent the adsorbent from disintegrating in water.
[0013] Carbonization is carried out by heating the organic matter in an inert gas atmosphere such as nitrogen gas or argon gas, an oxygen-free atmosphere, a low-oxygen atmosphere, a reducing atmosphere, or a reduced pressure atmosphere. 2 Pa or more 10 5 Low vacuum state below 10 Pa -1 Pa or more 10 2 Medium vacuum state below 10 Pa -5 Pa or more 10 -1 High vacuum state of 10 Pa or less -5 The carbonization can be carried out in an ultra-high vacuum state of 0.01 Pa or less. When the carbonization is carried out in a low-oxygen atmosphere, the oxygen concentration can be set to 0.01% to 3%, or 0.1% to 2%. The heating temperature in the carbonization can be 400°C to 1200°C, 500°C to 1100°C, 600°C to 1000°C, or 600°C to 900°C. The heating time can be 10 minutes to 10 days, or 10 minutes to 5 hours.
[0014] Carbonization is carried out using an internal combustion or external heat carbonization furnace. Examples of carbonization furnaces include batch-type closed charcoal kilns, continuous rotary kilns, rocking carbonization furnaces, and screw furnaces. Carbonization of biomass generates dry distillation gas, and produces porous charcoal with pores of various shapes and sizes, which are a complex mixture of pores due to the structure of the biomass and pores formed by the desorption of dry distillation gas. Dry distillation gas mainly contains combustible or reducing gases such as hydrogen, carbon monoxide, and alkanes such as methane, propane, and butane. Dry distillation gas is extracted at high temperatures (700°C to 1300°C), so its thermal energy and combustibility can be used as energy sources for power generation, hot water supply, etc.
[0015] Here, biomass refers to a type of organic matter, that is, a substance derived from a living organism and its metabolites. For example, materials derived from wood are examples of biomass. Specifically, examples include plank-shaped or column-shaped wood, thinning materials, pruning waste, construction waste wood, powdered sawdust, particle boats, and other wooden molded products. There are no restrictions on the type of wood, and it can be cedar, cypress, or bamboo. Other examples of biomass include agricultural waste such as rice husks, bagasse, corn cobs and leaves, and agricultural by-products such as straw, wheat straw, and hay. Other examples include plants that are the raw material for fibers, such as hemp, flax, cotton, sisal, abaca, and palm hair. Other examples include algae such as seaweed. Other examples include food waste and silage obtained from animal manure.
[0016] The size and shape of the porous carbide are not particularly limited, but the average particle size of the porous carbide may be 1 μm to 50 mm or 1 μm to 1 mm. By having the average particle size in this range, the porous carbide and the iron powder can be mixed uniformly in the mixing and kneading process described later.
[0017] Due to the pores formed inside, porous carbides have a large specific surface area. 2 / g or more 900m 2 / g or less, 100m 2 / g or more 800m 2 / g or less, or 150m 2 / g or more 400m 2 The specific surface area may be measured by a mercury intrusion method or a gas adsorption method such as the BJH method or the HK method.
[0018] 1-2.Iron and iron compounds As described later, iron is mixed with porous carbide as iron powder and supported. There is no restriction on the shape of the iron powder. For example, iron powder with an average circularity of 50 to 100, 70 to 95, or 80 to 90 may be used. The average circularity is one of the parameters that represent the shape of each iron particle contained in the iron powder, and is an average value obtained by analyzing an image obtained by observing the iron powder under a microscope, determining the circularity of a plurality of iron particles. As the circularity, for example, a value obtained by dividing the perimeter of a circle having an area equal to the area of the projection surface of each iron particle in the microscope image by the perimeter of the projection surface of each iron particle in the microscope image can be used. Alternatively, a value obtained by dividing the area of the projection surface by the area of a circle inscribed in the projection surface may be used as the circularity.
[0019] There is no restriction on the average particle size of the iron powder, and for example, iron powder having an average particle size in the range of 20 μm to 500 μm or 50 μm to 200 μm can be used. Furthermore, iron powder having a particle size distribution in which 1) the proportion of iron particles having a particle size in the range of 1 μm to less than 150 μm is 3% by mass to 70% by mass, 2) the proportion of iron particles having a particle size in the range of 1 μm to less than 75 μm is 0% by mass to 25% by mass, 3) the proportion of iron particles having a particle size in the range of 1 μm to less than 45 μm is 0% by mass to 15% by mass, 4) the proportion of iron particles having a particle size in the range of 150 μm to less than 2000 μm is 430% by mass to 99% by mass, and 5) the proportion of iron particles having a particle size in the range of 600 μm to less than 2000 μm is 0% by mass to 15% by mass, and at the same time, the sum of the proportion of iron particles of at least any one of 1) to 3) and the proportion of iron particles of 4) or 5) is 100% by mass may be used. Here, the average particle size of the iron powder is the average value of particle sizes determined by analyzing an image obtained by observing the iron powder under a microscope and determining the particle sizes of a plurality of iron particles. The particle size of each iron particle can be, for example, the diameter of a circle inscribed in the projection of each iron particle in the microscope image or the length of one side of a square.
[0020] The iron powder may contain trace amounts of other elements, such as carbon, oxygen, sulfur, phosphorus, manganese, silicon, vanadium, copper, titanium, etc. Thus, the purity of the iron powder may be 90.0% to 99.9% or 95.0% to 99.0%.
[0021] In addition, a part of the iron powder may be supported on the porous carbide in an oxidized state, that is, as an iron compound. Examples of the iron compound include iron oxide and iron hydroxide. The iron contained in the iron compound may be present in a divalent, trivalent, or mixed valence state in which divalent and trivalent valences are mixed. Therefore, when the iron compound is iron hydroxide, it may be ferrous hydroxide or ferric hydroxide. When the iron compound is iron oxide, it may be wustite (FeO), hematite or maghemite (Fe2O3), or magnetite (Fe3O4).
[0022] 1-3. Binder The binder is used to efficiently disperse the porous carbide and iron powder in the kneading process described later, and to integrate the iron or iron compounds with the porous carbide. There is no restriction on the type of binder, and organic and / or inorganic binders can be used. Examples of organic binders include one or more selected from molasses, blackstrap molasses, starch, dextrin, corn starch, rice bran, polyvinyl alcohol, a copolymer of vinyl acetate and ethylene or a saponified form thereof, pulp waste liquor, lignin sulfonate, carboxymethylcellulose, hydroxypropylmethylcellulose, sodium alginate, phenolic resin, and tar pitch. Among them, molasses is inexpensive, contains few harmful components, and contains many solid components, so that the use of molasses makes it easy to form the adsorbent. Examples of inorganic binders include cement, ground granulated blast furnace slag, fly ash, gypsum (calcium sulfate), calcined gypsum obtained by heating and dehydrating gypsum, and sodium silicate.
[0023] 1-4. Carbonates and bicarbonates By using biomass as the raw material for the porous carbide, the alkali metal or alkaline earth metal compounds contained in the biomass remain in the porous carbide. These metal compounds are contained in the porous carbide as, for example, halides, oxides, hydroxides, sulfates, or nitrates. As described below, in the manufacturing process of the adsorbent, the alkali metal or alkaline earth metal compounds are converted into carbonates and / or hydrogen carbonates by reaction with carbon dioxide, and are supported on the porous carbide (carbonation). In other words, the alkali metal or alkaline earth metal compounds function as reaction sites for carbon dioxide.
[0024] Specific examples of alkali metals include sodium, potassium, lithium, and cesium. Alkaline earth metals include magnesium and calcium. Therefore, examples of carbonates and bicarbonates contained in the adsorbent include sodium carbonate, potassium carbonate, lithium carbonate, cesium carbonate, magnesium carbonate, calcium carbonate, sodium bicarbonate, potassium bicarbonate, lithium bicarbonate, cesium bicarbonate, magnesium bicarbonate, and calcium bicarbonate.
[0025] The adsorbent may contain compounds of alkali metals or alkaline earth metals other than carbonates and hydrogen carbonates that remain without reacting with carbon dioxide. That is, the adsorbent may contain one or more of the chlorides, oxides, hydroxides, sulfates, and nitrates of the above metals, together with the carbonates or hydrogen carbonates of metals selected from alkali metals and alkaline earth metals.
[0026] Alternatively, the carbonates or hydrogencarbonates of alkali metals or alkaline earth metals may be formed by adding compounds of alkali metals and / or alkaline earth metals separately during the production of the adsorbent and then reacting them with carbon dioxide. In this case, the content of the carbonates or hydrogencarbonates of alkali metals or alkaline earth metals can be adjusted freely without being restricted by the compounds of alkali metals or alkaline earth metals contained in the biomass.
[0027] 1-5.Composition ratio The composition ratio of the above-mentioned configuration can be adjusted appropriately. For example, the content of the porous carbide in the adsorbent may be adjusted in the range of 20% by mass to 80% by mass, 40% by mass to 80% by mass, or 60% by mass to 80% by mass. The sum of the contents of iron and iron compounds may be adjusted in the range of 5% by mass to 35% by mass, 5% by mass to 25% by mass, or 5% by mass to 20% by mass. The content of the binder may be adjusted in the range of 5% by mass to 50% by mass, 15% by mass to 50% by mass, or 20% by mass to 50% by mass. The sum of the contents of carbonates and hydrogen carbonates of metals selected from alkali metals and alkaline earth metals may be adjusted in the range of 1% by mass to 30% by mass, 1% by mass to 15% by mass, or 1% by mass to 10% by mass.
[0028] Alternatively, the carbon content in the adsorbent may be adjusted from a range of 10% by mass to 80% by mass. The iron content in the adsorbent (i.e., iron element including zero-valent iron and / or iron ions) may be adjusted from a range of 5% by mass to 35% by mass. The sum of the alkali metal and alkaline earth metal contents may be adjusted from a range of 1% by mass to 30% by mass.
[0029] In measuring the content of the porous carbide in the adsorbent, first, the carbon content of the porous carbide in the raw material stage is measured. For example, a method conforming to JIS H1617, JIS Z2615, and ASTM E1941 may be adopted using the combustion and infrared absorption method. Specifically, the porous carbide in the raw material stage is burned in an oxygen stream in a combustion furnace to generate carbon dioxide. The generated carbon dioxide is introduced into an infrared analyzer using oxygen gas, and its absorption is measured with a detector to determine the carbon dioxide concentration. From this carbon dioxide concentration, the mass of carbon in the porous carbide in the raw material stage is quantified as the mass of the porous carbide. After that, the content of the porous carbide may be calculated from the mass of the porous carbide in the raw material stage and the other raw materials such as the binder, iron powder, and water that are mixed with the porous carbide. The content of the binder may also be calculated from the mass of the other raw materials such as the porous carbide, iron powder, and water used in the manufacturing process of the adsorbent.
[0030] The sum of the iron and iron oxide contents, and the sum of the carbonate and hydrogen carbonate contents of a metal selected from alkali metals and alkaline earth metals can be measured, for example, by applying inductively coupled plasma optical emission spectroscopy (ICP-OES) or inductively coupled plasma mass spectrometry (ICP-MS) to the adsorbent. In ICP-OES, argon plasma is used as the light source, and a mist of the solution sample is introduced into the plasma to disperse the spectra specific to the alkali metals and alkaline earth metals, and the alkali metals and alkaline earth metals can be quantified from the measured wavelength and emission intensity. In ICP-MS, argon plasma is used as the ion source to ionize the elements contained in the sample, and the ions are separated and detected based on their mass-to-charge ratio. The elements can be identified from the mass-to-charge ratio of the detected ions, and the alkali metals and alkaline earth metals can be quantified by counting the detected ions. In addition, the sum of the carbonate and hydrogen carbonate contents of a metal selected from alkali metals and alkaline earth metals can be obtained by converting the quantified alkali metal and alkaline earth metal ion contents into carbonate or hydrogen carbonate.
[0031] In addition, the above-mentioned method does not take into account the treatment with a gas containing carbon dioxide, which will be described later, i.e., the reaction rate between the alkali metal salt or alkaline earth metal salt contained in the porous carbide and carbon dioxide, or the mass change of the adsorbent due to this reaction. In addition, the generation of iron compounds due to the oxidation of iron in the manufacturing process is not taken into account. However, since the mass change due to these reactions is within a negligible range, it can be said that the reliability of the measurement results by the above-mentioned method is sufficiently high.
[0032] On the other hand, the carbon content in the adsorbent can be determined by applying the above-mentioned combustion and infrared absorption method to the adsorbent. The carbon content in the adsorbent is mainly the carbon content derived from the porous carbide and binder, and from carbonates and hydrogen carbonates of metals selected from alkali metals and alkaline earth metals. The iron content and the sum of the alkali metal and alkaline earth metal contents can also be measured by applying ICP-OES or ICP-MS to the adsorbent.
[0033] By adjusting the content of each component within the above range, it is possible to obtain the function of effectively removing phosphate from water and prevent the adsorbent from disintegrating in water, thereby enabling the water quality improvement function to be maintained for a long period of time.
[0034] The phosphate adsorption capacity of an adsorbent can be determined, for example, by a batch test. A batch test is a method in which the amount of adsorbed phosphate is calculated from the difference between the phosphate concentration of a solution containing the adsorbed phosphate and the phosphate concentration of the solution after the phosphate is adsorbed. The phosphate concentration can be determined, for example, by the molybdenum blue method or the ammonium vanadomolybdate absorbance method. In the former, a potassium peroxodisulfate solution is added to a certain amount of sample taken and heated, and a mixed solution of ammonium molybdate and dipotassium bis[(+)-tartrate]diantimonate(III) trihydrate is added to generate molybdophosphoric acid. An L-ascorbic acid solution is added to this molybdophosphoric acid to generate molybdenum blue (hydrated mixed-valence oxide of molybdenum). The amount of water-soluble phosphate is quantified by measuring the absorption of molybdenum blue (for example, absorption at 880 nm) using an ultraviolet-visible spectrophotometer. In the latter, nitric acid (1+1) is added to a certain amount of sample taken and heated to hydrolyze non-orthophosphate to orthophosphate ions. Ammonium vanadate(V), hexaammonium heptamolybdate, and nitric acid are then added to form vanadophosphoric acid molybdate, and the phosphate is quantified by measuring the absorbance of vanadophosphoric acid molybdate (e.g., at 420 nm) using a UV-Vis spectrophotometer.
[0035] 2. Manufacturing method An example of a method for producing an adsorbent will be described below. Figures 1 and 2 are a flow chart and a scheme, respectively, showing a method for producing an adsorbent. x A y is a compound of an alkali metal or alkaline earth metal contained in the porous carbide. M is selected from Li, Na, K, Cs, Mg, and Ca, and A is exemplified by F, Cl, Br, I, OH, O, SO4, and NO3. x and y are each independently 1 or 2 depending on the valence of the anion A and the metal M.
[0036] 2-1.Mixing and kneading As shown in FIG. 1 and FIG. 2, first, the porous carbide, binder, and iron (iron powder) as raw materials are mixed and then kneaded (mixed). As described above, it is preferable to use carbide obtained by carbonizing biomass as the porous carbide. As the iron powder, iron powder having the average particle size or particle size distribution described above may be used. The amounts of the porous carbide, binder, and iron powder are appropriately adjusted so that the composition ratio falls within the range described above. The porous carbide may be crushed or classified in advance to adjust its particle size. Since the particle size of the porous carbide is often larger than that of the iron powder, the porous carbide may be crushed so that the particle size is approximately the same as that of the iron powder.
[0037] When mixing or kneading, water is added to the porous carbide, binder, and iron as necessary. By adding water, it is possible to prevent dust generation and to mix the porous carbide and iron powder more uniformly.
[0038] A kneader can be used to mix and knead these raw materials. As the kneader, for example, a single-screw kneader, a twin-screw kneader, a mixing roll, a kneader, or a Banbury mixer can be used. A kneader having both mixing and kneading functions can also be used. In this case, the porous carbide, iron powder, and binder are charged into the kneader, and then mixed and kneaded. Alternatively, mixing and kneading can be performed continuously. For example, the porous carbide and iron powder are charged into the kneader and mixed, and then the binder is charged into the kneader and kneaded. The binder may be added all at once, intermittently, or continuously. By adding the binder after mixing the porous carbide and iron powder and kneading, it is possible to prevent the porous carbide and iron powder from agglomerating and suppress foaming.
[0039] The kneading temperature can be set arbitrarily, for example, from 0° C. to 50° C., or from 10° C. to 40° C. The kneading time can also be set appropriately in consideration of the mixing ratio and amount of the raw materials, the type of binder, the capacity of the kneader, and the like, and can be set within the range of, for example, from 1 second to 1 hour, from 1 minute to 30 minutes, or from 1 minute to 15 minutes.
[0040] By the above operations, a paste-like precursor in which the porous carbide, binder, and iron powder are mixed can be obtained. In this process, a part of the iron powder may be oxidized, and as a result, the precursor contains compounds containing divalent and / or trivalent iron (Fe(II), Fe(III)). As mentioned above, examples of iron compounds include iron hydroxide and iron oxide. In addition, during mixing and kneading, compounds of alkali metals and / or alkaline earth metals other than carbonates and hydrogen carbonates may be added.
[0041] 2-2. Granulation As an optional step, the precursor may be granulated and molded into a certain shape. The precursor may be molded using a granulator. Examples of the granulator include a compression granulator, an extrusion granulator, a roll granulator, a blade granulator, a melt granulator, or a spray granulator.
[0042] When using an extrusion type granulator, a paste-like precursor formed into a predetermined shape is extruded from a die attached to the granulator. The extruded precursor is cut into a predetermined length and formed into a pellet shape in which the extrusion direction is the height direction. The length of the precursor (the height of the pellet shape) can be adjusted by adjusting the extrusion speed and cutting speed of the precursor in the extrusion type granulator (the rotation speed of the cutter in the case of a rotary cutting method). In addition, the diameter of the precursor (the diameter when the cross-sectional shape is circular) can be adjusted by adjusting the opening diameter of the die. Therefore, by using an extrusion type granulator, a precursor having a pellet shape with a controlled size (for example, a roughly cylindrical shape) can be obtained.
[0043] For example, the length of each pellet may be from 1 mm to 20 mm, from 3 mm to 15 mm, or from 6 mm to 12 mm. If the cross-sectional shape is circular, the diameter of the pellet may be from 1 mm to 20 mm, from mm to 10 mm, or from 3 mm to 8 mm.
[0044] The cross-sectional shape of the precursor after molding (cross-section perpendicular to the longitudinal direction) is not limited to a circle. The cross-sectional shape of the precursor may be, for example, an ellipse or a polygon. That is, the precursor after molding may be in the form of a pellet of an elliptical cylinder or a polygonal cylinder, as well as a cylinder. The cross-sectional shape of the precursor can be changed by changing the opening shape of the die. This granulation process may be performed after the drying process described later.
[0045] 2-3. Carbon dioxide treatment The precursor is subsequently treated with carbon dioxide. Specifically, the precursor is brought into contact with a gas containing carbon dioxide, and all or a part of the alkali metal or alkaline earth metal compounds contained in the porous carbide of the precursor are converted to carbonates or hydrogen carbonates. The gas is carbon dioxide or a mixed gas of carbon dioxide and other gases, and examples of the other gases include air, nitrogen, oxygen, rare gases such as argon, and water (water vapor). In the case of a mixed gas, the carbon dioxide concentration in the gas can also be set arbitrarily, and may be appropriately set within the range of, for example, 1% by volume or more and 100% by volume or less, 1% by volume or more and 50% by volume or less, or 1% by volume or more and 20% by volume or less.
[0046] The contact of the precursor with carbon dioxide may be carried out, for example, by introducing a gas containing carbon dioxide into a kneader and simultaneously with kneading. Alternatively, the precursor after kneading or molding may be placed in a container made of glass or stainless steel, and a gas containing carbon dioxide may be introduced into the container. Alternatively, the precursor after molding may be brought into contact with the gas containing carbon dioxide while rotating in a pan-type granulator. The temperature in this treatment may be, for example, 0°C to 80°C or 0°C to 50°C, and is typically room temperature (25°C or thereabouts). The humidity may be 20% to 95%, or 50% to 90%.
[0047] An example of a source of the gas containing carbon dioxide is a cylinder or tank of the gas containing carbon dioxide. Alternatively, exhaust gas from a facility that emits a large amount of carbon dioxide (such as a chemical plant, a waste incineration facility, a thermal power plant, or various other factories) or purified carbon dioxide obtained by subjecting the exhaust gas to dust removal, desulfurization, denitrification, etc. may be used. When facilities that emit a large amount of carbon dioxide are close to the manufacturing site of the adsorbent, these facilities function as a source of the gas containing carbon dioxide, thereby reducing the cost of transporting carbon dioxide and preventing secondary emissions of carbon dioxide associated with the transportation.
[0048] Through the above steps, an adsorbent is obtained.
[0049] 2-4. Drying As an optional step, the adsorbent obtained by the carbon dioxide treatment may be dried. The drying temperature and time are also appropriately selected depending on the amount of the adsorbent and the amount of water contained. For example, the drying temperature may be selected from the range of 30°C or more and less than 400°C, 50°C or more and less than 300°C, or 100°C or more and less than 300°C. The humidity during drying may be 20% or more and less than 95%, or 50% or more and less than 90%. The drying time may also be appropriately selected from the range of 1 minute or more and less than 1 week, 1 hour or more and less than 3 days, or 3 hours or more and less than 1 day. The atmosphere during drying may be, for example, air, nitrogen, a rare gas such as argon, or a mixture of these.
[0050] In the manufacture of an adsorbent according to one embodiment of the present invention, high temperature firing is not required. In other words, heating to a temperature (e.g., 400°C or higher) required to carbonize the binder is not required. In other words, the maximum temperature in the manufacturing process of the adsorbent may be less than 400°C. This eliminates the need for the time and energy required for firing, making it possible to provide an adsorbent at a lower cost.
[0051] As described above, in the method for producing an adsorbent according to one embodiment of the present invention, all or part of the compounds of alkali metals and / or alkaline earth metals contained in the porous carbide are converted to carbonates or hydrogen carbonates. As a result, the adsorbent contains at least one of carbonates and hydrogen carbonates of alkali metals, and carbonates and hydrogen carbonates of alkaline earth metals. Although the detailed mechanism is unclear, when carbonates and / or hydrogen carbonates of metals selected from alkali metals and alkaline earth metals are contained, the adsorbent is prevented from collapsing in water. That is, even if the adsorbent is placed in water or water containing an adsorbent for a long period of time, it is hardly eroded by water and its shape can be stably maintained. Therefore, it can be used as an adsorbent for improving water quality for a long period of time, and can be easily recovered after adsorption.
[0052] <Second embodiment> In this embodiment, a system that contributes to reducing carbon dioxide in the atmosphere through the adsorbent described in the first embodiment will be described with reference to FIG.
[0053] As described in the first embodiment, in the production of an adsorbent according to one embodiment of the present invention, a porous carbonized material obtained from biomass can be used as one of the raw materials. In this case, the dry distillation gas obtained by carbonizing the biomass can be used as an energy source to generate electricity and produce hot water (FIG. 3, (1)).
[0054] The obtained porous carbide is mixed and kneaded with iron powder and a binder to give a precursor (Figure 3, (2)), which is then further treated with a gas containing carbon dioxide (Figure 3, (3)). As a result, an adsorbent is obtained that supports iron or iron compounds and contains alkali metal carbonates and hydrogen carbonates, alkaline earth metal carbonates and hydrogen carbonates, etc. As mentioned above, carbides supporting iron and iron compounds effectively adsorb pollutants in water, especially phosphorus-containing compounds such as phosphoric acid. Therefore, by installing this adsorbent in water bodies such as rivers, lakes, and seas, water quality can be improved (Figure 3, (4)).
[0055] Phosphate adsorbed to the adsorbent is a typical component of nutrients that promotes the growth of various plants. Therefore, the adsorbent adsorbing phosphate can be used as fertilizer, which contributes to providing fertilizer at a low cost. For example, the adsorbent subjected to water quality improvement treatment can be spread on farmland as it is or after crushing and classification (Figure 3, (5)). Alternatively, it may be spread after mixing with fertilizer assistants such as calcium sulfate or other fertilizer components. The fertilizer components to be added include one or more selected from nitrogen, potassium, calcium, magnesium, manganese, silicic acid, and boron. Specific examples of materials include oil cake, flavored chicken manure, fish meal, bone meal, rice bran, bat guano, pocassi fertilizer, wood ash, lime, and chemical fertilizer.
[0056] The sprayed adsorbent slowly releases the adsorbed phosphate, which is used for plant growth. During this process, the plants use carbon dioxide in the atmosphere as a carbon source for photosynthesis and grow (Fig. 3, (6)). The plants are then used in a variety of ways, including as food or materials. After use, the plants can be reused as biomass to produce porous charcoal (Fig. 3, (7)).
[0057] In this way, by applying the embodiment of the present invention, a cycle is established, which includes the production of porous charcoal from biomass, the production of adsorbents, water quality improvement and fertilizer production, the growth of plants that use the fertilizer, and the regeneration of biomass. In this cycle, the carbon dioxide in the atmosphere fixed by the plants is used as a carrier for iron and iron compounds that exhibit phosphate adsorption function, and is stored in the ground in the form of carbon. Therefore, this cycle is a system that reduces and stores carbon dioxide in the atmosphere in the ground, and contributes to reducing carbon dioxide in the atmosphere. EXAMPLES
[0058] In this example, the preparation of an adsorbent according to one embodiment of the present invention and the results of evaluating the adsorbent will be described.
[0059] 1. Preparation of Adsorbent 1-1.Example As the raw material, porous carbonized material, irregularly shaped charcoal (waste charcoal from wood biomass gasification power generation) was used. 15 g of iron powder, in which the ratio of iron particles having a particle size in the range of 300 μm to 2000 μm is 45 mass%, the ratio of iron particles having a particle size in the range of 75 μm to less than 300 μm is 45 mass%, and the ratio of iron particles having a particle size in the range of 1 μm to less than 75 μm is 10 mass%, and 35 g of calcined gypsum were added to 45 g of this charcoal and mixed with a spatula for 1 minute. Furthermore, 7 g of blackstrap molasses (solid content 70%) and 40 mL of water were added to this mixture at room temperature and kneaded for 30 minutes to obtain a powder mixture. The solid content ratio of charcoal, iron powder, calcined gypsum, and blackstrap molasses was 45:15:5:35 (total 100%).
[0060] Next, the obtained powder mixture was charged into a granulator and formed into pellets having a diameter of 6 mm and a height of 9 mm.
[0061] Next, 50 g of the molded powder mixture was sealed in a glass container of about 5 L, and carbon dioxide (100% purity) was introduced into the container at 20° C. The flow rate of carbon dioxide was 5 mL / min, and the gas was introduced for 18 hours.
[0062] 1-2.Comparative Example As a comparative example, an adsorbent was prepared in the same manner as in the example, except that the treatment with a gas containing carbon dioxide was not carried out and the adsorbent was allowed to stand in a container at the same temperature for the same period of time.
[0063] 2. Evaluation The adsorption amount of phosphoric acid of the adsorbent of the example was evaluated using a batch method. 0.1 g of the adsorbent of the example was added to 50 mL of 200 mg / L phosphoric acid solution, and the mixture was horizontally shaken at 23°C and 100 rpm until the equilibrium concentration was reached, and then filtered. The phosphorus concentration of the filtrate was quantified by molybdenum blue absorptiometry, and the adsorption amount of phosphorus was 34 (mg-P / g). From this, it was confirmed that the adsorbent according to one embodiment of the present invention exhibits high phosphate adsorption ability. On the other hand, the adsorption amount of phosphorus of the adsorbent of the comparative example was 29 (mg-P / g).
[0064] A photograph of the Example after phosphate adsorption is shown in Figure 4. In this photograph, the black colored parts are the adsorbent. As can be seen from Figure 4, no collapse was observed in the adsorbent of the Example treated with a gas containing carbon dioxide, and it was found that the shape was stably maintained in water. On the other hand, the adsorbent of the Comparative Example collapsed in water.
[0065] These results indicate that by contacting a precursor containing porous carbide, a binder, and iron powder with carbon dioxide, it is possible to form a carbonate of a metal selected from alkali metals and alkaline earth metals in the adsorbent, and that it is possible to increase the shape stability in water of the resulting adsorbent without impairing its phosphate adsorption ability.
[0066] The above-described embodiments of the present invention may be combined as appropriate as long as they are not mutually inconsistent. Any embodiment in which a person skilled in the art appropriately adds or deletes components or modifies the design based on each embodiment is also included in the scope of the present invention as long as it includes the gist of the present invention.
[0067] Even if there are other effects and advantages different from those brought about by the respective embodiments described above, those which are clear from the description in this specification or which can be easily predicted by a person skilled in the art are naturally understood to be brought about by the present invention.
Claims
1. Porous charcoal derived from biomass, Binder, Iron, and At least one of a carbonate and a hydrogen carbonate of a metal selected from an alkali metal and an alkaline earth metal, The content of the porous carbide is 20% by mass or more and 80% by mass or less, The content of the binder is 5% by mass or more and 50% by mass or less, The adsorbent, wherein a sum of the contents of the carbonate and the hydrogen carbonate is 1 mass % or more and 10 mass % or less.
2. The adsorbent of claim 1 further comprising an iron compound.
3. The adsorbent according to claim 2 , wherein the sum of the content of said iron and said iron compound is 5 mass % or more and 35 mass % or less.
4. 3. The adsorbent of claim 2, wherein the iron compound is selected from iron oxide and iron hydroxide.
5. 2. The adsorbent of claim 1, wherein the metal is selected from sodium, potassium, magnesium, and calcium.
6. 2. The adsorbent according to claim 1, wherein the binder is selected from molasses, blackstrap molasses, starch, dextrin, corn starch, rice bran, polyvinyl alcohol, a copolymer of vinyl acetate and ethylene or a saponified form thereof, pulp waste liquor, lignin sulfonate, carboxymethylcellulose, hydroxypropylmethylcellulose, sodium alginate, phenolic resin, tar pitch gypsum, cement, ground granulated blast furnace slag, fly ash, calcined gypsum, and sodium silicate.
7. A method for producing an adsorbent comprising: a porous charcoal derived from biomass; a binder; iron; and at least one of a carbonate and a hydrogen carbonate of a metal selected from an alkali metal and an alkaline earth metal, Mixing the porous carbide with a binder and iron powder to prepare a precursor; treating the precursor with a gas comprising carbon dioxide; The concentration of the carbon dioxide in the gas is 1% by volume or more and 100% by volume or less, In the adsorbent, The content of the porous carbide is 20% by mass or more and 80% by mass or less, The content of the binder is 5% by mass or more and 50% by mass or less, The production method, wherein a sum of the contents of the carbonate and the hydrogencarbonate is 1 mass % or more and 10 mass % or less.
8. The method of claim 7 further comprising forming the precursor into pellets prior to said treatment with said gas.
9. The method of claim 7 , wherein the porous carbide further comprises a compound of the metal.
10. The method of claim 9, wherein the compound is selected from the chlorides, oxides, hydroxides, sulfates, and nitrates of the metal.
11. 8. The method according to claim 7, wherein the binder is selected from the group consisting of molasses, blackstrap molasses, starch, dextrin, corn starch, rice bran, polyvinyl alcohol, a copolymer of vinyl acetate and ethylene or a saponified product thereof, pulp waste liquor, lignin sulfonate, carboxymethylcellulose, hydroxypropylmethylcellulose, sodium alginate, phenolic resin, tar pitch gypsum, cement, ground granulated blast furnace slag, fly ash, calcined gypsum, and sodium silicate.
Citation Information
Patent Citations
Oxygen absorbent
JP1984052528A
Agent for removing tetrachloroethylene in water and preparation thereof
JP1992190847A
Oxygen absorber for increasing purity of nitrogen gas separated from compressed air
JP2004098037A
Phosphorus recovering material, its producing method and its effectiveness as fertilizer
JP2007075706A
Environmental cleanup tool using tennis ball, manufacturing method, use method and application thereof
JP2017225964A